eCM 2013
DOI: 10.22203/ecm.v026a02
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cartilage fragments in a composite scaffold for one stage osteochondral repair in a goat model

Abstract: We propose a culture-free approach to osteochondral repair with minced autologous cartilage fragments loaded onto a scaffold composed of a hyaluronic acid (HA)-derived membrane, platelet-rich fibrin matrix (PRFM) and fibrin glue. The aim of the study was to demonstrate in vitro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 55 publications
1
36
1
Order By: Relevance
“…The importance of removing the calcified cartilage layer for the formation of repair tissue by the original microfracturing technique has recently been demonstrated in a horse model . Thus, a significant portion of the cells within the forming repair tissue of recent successful repair approaches may not origin from the cartilage grafts themselves but rather from the bone marrow. Nevertheless, transplanted cartilage grafts may exert an immanent beneficial role by supporting chondrogenic differentiation of ingrowing mesenchymal repair cells, since cartilage tissue or chondrocytes were shown to exert significant pro‐chondrogenic paracrine effects …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of removing the calcified cartilage layer for the formation of repair tissue by the original microfracturing technique has recently been demonstrated in a horse model . Thus, a significant portion of the cells within the forming repair tissue of recent successful repair approaches may not origin from the cartilage grafts themselves but rather from the bone marrow. Nevertheless, transplanted cartilage grafts may exert an immanent beneficial role by supporting chondrogenic differentiation of ingrowing mesenchymal repair cells, since cartilage tissue or chondrocytes were shown to exert significant pro‐chondrogenic paracrine effects …”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] In rabbit and goat models, transplanted native cartilage fragments contributed to the formation of better repair tissue in treated cartilage defects than application of the scaffolds alone. 6,[8][9][10] Successful results following transplantation of autologous cartilage fragments or allogeneic particulated juvenile articular cartilage were also observed in large animal models 11 and human studies. 12,13 A variety of biodegradable scaffolds have been used for embedding the cartilage fragments.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The other primary focus of laboratory research has been the development of a composite scaffold for the delivery of autologous particulated cartilage [15][16][17]. The authors demonstrated in a rabbit model that chondral defects of the knee could be effectively treated with autologous particulated cartilage delivered in a composite scaffold made of hyaluronic acid felt, fibrin glue, and platelet rich plasma [16].…”
Section: Laboratory Researchmentioning
confidence: 99%
“…The authors demonstrated in a rabbit model that chondral defects of the knee could be effectively treated with autologous particulated cartilage delivered in a composite scaffold made of hyaluronic acid felt, fibrin glue, and platelet rich plasma [16]. These results were then replicated in a goal model [17]. However, they have not shown superiority of this technique to simple transplantation of autologous particulated cartilage in fibrin glue.…”
Section: Laboratory Researchmentioning
confidence: 99%